The Role of Myo-Inositol in the Management of Metabolic and Reproductive Sequelae of Polycystic Ovary Syndrome: A Comprehensive Review of the Current State of Knowledge - Bullmann, Agnieszka Irena; Baran, Julia; Wojciechowska, Karolina; Choroszewska, Ewelina; Warych, Wiktor; Niezgoda, Julia; Skłodowski, Tomasz; Woroniecka, Katarzyna (Quality in Sport, 2026)
Polycystic Ovary Syndrome (PCOS) represents a heterogeneous and multifaceted endocrinopathy, characterized by extensive metabolic implications, affecting a substantial global cohort of reproductive-age women. Central to its pathogenesis is insulin resistance (IR) and compensatory hyperinsulinemia, which drive both metabolic dysfunction and reproductive failures. Myo-inositol (MI), acting as a vital second messenger for both insulin and follicle-stimulating hormone (FSH), has emerged as a cornerstone therapeutic agent. This comprehensive review evaluates the clinical efficacy of MI, particularly when administered in the physiological 40:1 ratio with D-chiro-inositol (DCI). We analyze its impact on glycemic profiles, hormonal stabilization, and the enhancement of oocyte competence. Based on the 2023 International Evidence-based Guidelines and recent clinical trials, MI represents a safe, well-tolerated, and effective alternative to traditional pharmacological interventions, providing a holistic approach to PCOS management.